APLIKASI PENILAIAN ANGKA KREDIT DOSEN DALAM MENUNJANG PROSES PENGAJUAN JABATAN FUNGIONAL DOSEN PADA STMIK HANG TUAH PEKANBARU - Herianto .; Akhmad Zulkifli; Yulanda . (Jurnal Ilmu Komputer, 2017)
The increase of functional position is one of the process that must be passed by a lecturer in order to improve the career of his rank or position. Specifically for a lecturer, the promotion process is a form of assessment on the performance of lecturers based on the implementation of Tri Dharma Perguruan Tinggi in the form of research, teaching and devotion to the community. STMIK Hang Tuah Pekanbaru lecturer credit calculation process is still done conventionally, where lecturers have to enter data related to the credit numbers manually to the personnel, as well as the calculation of the credit score is still calculated by the lecturer is also by manual means which are further computed with microsoft excel application. With this condition, the process will take a long time, and the possibility of error in input large enough because it is still done conventionally. to speed up the process of calculating the credit score as well as to minimize the occurrence of error input and calculation of credit numbers it is necessary to design a web-based applications that can help lecturers and staff so that expected to make the work more effective and efficient.